“Redefining the Fortress” Migrant Experiences, Adaptation and Connection within Serbian Borderlands - Leone, Nicholas J (AUC Knowledge Fountain, 2025)
Abstract This thesis seeks to examine migrant experiences due to Serbia's geopolitical significance along the so-called Balkan route, and how this is specifically exemplified in the northern autonomous region of Vojvodina. Serbia’s position outside the external border of the European Union has caused it to be a strategic transit point for migrants en route to desired destinations, typically within Western and Northern Europe. However, the European Union’s externalization policies in partnership with Serbian authorities have played an extensive role in migration mobility patterns and humanitarian conditions for migrants traversing within the Serbian borderlands, specifically along the border with Hungary. The militarization of borders, surveillance technologies, and inhumane pushbacks by Serbian police and Frontex have forced many migrants to remain in Serbia for extended periods, placing them in highly precarious situations. As these pressures increase, NGOs have also been negatively affected as their own capacity to provide essential services and aid towards migrants have been limited due to the rising state measures utilized to slow or halt their operations. This research explores how migrants navigate and maneuver the inherent precarity amidst these particular borderlands. It addresses the tools within their own decision making that migrants may utilize along the route to navigate the daily ripples of the restrictive policies, including transnational solidarity networks, NGOs, or navigating smuggling dynamics in an attempt to mitigate these circumstances. The study aims to dismantle the notion of “Fortress Europe” as an indestructible force and shift agency back to the individual migrant, and investigate the relationship between the EU’s restrictive policies and migrant mobilities, focusing on how migrants adapt and exercise agency despite institutional violence and restrictions. Through an in-depth literature review, analysis of migration regimes, as well as interviews with migrants, NGOs, and other stakeholders, the study will contribute to understanding the broader implications of border securitization and externalization on human rights and migrant mobility in the region.